Penyuluhan dan Edukasi Potensi Sumber Daya Alam Sekitar Sebagai Bahan Baku Obat dan Pangan Fungsional Desa Marinsow Likupang Minahasa Utara: Counseling and Education on the Potential of Environmental Natural Resources as Raw Materials for Medicine and Functional Food in Marinsow Village, Likupang, North Minahasa - Pandiangan, Dingse; Nainggolan, Nelson; Maramis, Redway Truman Douglas (Sam Ratulangi University, 2025)
Marinsow Village, located in East Likupang District, North Minahasa Regency, North Sulawesi Province, has a wealth of biological natural resources that have great potential to be developed as raw materials for traditional medicine and functional food. Unfortunately, the use of this potential by the local community is still limited, both due to limited knowledge and the lack of accessible scientific information. Based on these conditions, this community service activity was carried out with the aim of providing counseling and education to the people of Marinsow Village about the types of local plants that have medicinal properties and potential as functional food with high economic and health value. The method of implementing the activity is carried out through a participatory approach in the form of interactive lectures, group discussions, and demonstrations of simple processing of natural materials into value-added products. The results of the activity show high community enthusiasm and increased knowledge and understanding of the importance of conservation and wise use of local natural resources. Some plants that were previously considered wild are now starting to be considered for cultivation, such as turmeric, curcuma leaves, moringa leaves, and ginger. It is hoped that in the future, the people of Marinsow Village can develop herbal products and functional foods based on local wisdom that not only increase family health resilience, but also open up new economic opportunities based on village potential. This activity is expected to be the first step towards the sustainable development of healthy and independent villages. ABSTRAK Desa Marinsow, yang terletak di Kecamatan Likupang Timur, Kabupaten Minahasa Utara,Provinsi Sulawesi Utara, memiliki kekayaan sumber daya alam hayati yang sangat potensial untukdikembangkan sebagai bahan baku obat tradisional dan pangan fungsional. Sayangnya,pemanfaatan potensi tersebut oleh masyarakat setempat masih terbatas, baik karena keterbatasanpengetahuan maupun minimnya informasi ilmiah yang dapat diakses. Berdasarkan kondisitersebut, kegiatan pengabdian masyarakat ini dilaksanakan dengan tujuan untuk memberikanpenyuluhan dan edukasi kepada masyarakat Desa Marinsow mengenai jenis-jenis tumbuhan lokalyang memiliki khasiat obat serta potensi sebagai pangan fungsional yang bernilai ekonomi dankesehatan tinggi. Metode pelaksanaan kegiatan dilakukan melalui pendekatan partisipatif berupaceramah interaktif, diskusi kelompok, dan demonstrasi pengolahan sederhana bahan alam menjadiproduk bernilai tambah. Hasil kegiatan menunjukkan antusiasme masyarakat yang tinggi sertameningkatnya pengetahuan dan pemahaman tentang pentingnya konservasi dan pemanfaatansumber daya alam lokal secara bijak. Beberapa tanaman yang sebelumnya dianggap liar kini mulaidipertimbangkan untuk dibudidayakan, seperti kunyit, temulawak, daun kelor, dan jahe. Harapanke depannya, masyarakat Desa Marinsow dapat mengembangkan produk herbal dan panganfungsional berbasis kearifan lokal yang tidak hanya meningkatkan ketahanan kesehatan keluarga,tetapi juga membuka peluang ekonomi baru berbasis potensi desa. Kegiatan ini diharapkan menjadilangkah awal menuju pengembangan desa sehat dan mandiri secara berkelanjutan.